ANALISIS UMUR SISA DAN TEBAL PERKERASAN JALAN TOL AKIBAT BEBAN BERLEBIH - Ahmad Ahlan Hidayah Ahmad Gumelar; Nuzul Barkah Prihutomo; Danang Eko Saputro (Construction and Material Journal, 2022)
Toll Road is an important instrument in people's lives because it can shorten travel time, cut travel costs, economic growth in the area. This makes the Toll Road the main choice for people to travel. The economic growth of an area causing the growth of industrial estates is in line with the growth of vehicles and the vulnerability of vehicles that are classified as excessive loads. Jakarta-Cikampek toll road passes through an industrial area that allows overload vehicles pass the section. Excessive load vehicles will damage the road and reduce the life of previously designed plans. This study aims to find out the impact caused by excessive load vehicles on the age of the road plan and evaluate the need for thick road pavement due to excessive load vehicles. Based on the calculation of the remaining age of the pavement obtained the results for vehicle overload by 3.21% with the remaining life of the pavement by 6 months. Meanwhile, for the remaining age in vehicle overload group 6B in 2032 by 3.48%. Then for the calculation of the thickness of the pavement needed obtained a result of 35 cm. Based on these results, it can be concluded that excessive vehicles have an impact on the pavement of the toll road. Keywords: Excessive Load Vehicles, Pavement Thickness, The Lifespan of Pavement.